STRATEGI PEMASARAN DIGITAL MELALUI MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN BRAND AWARENESS PADA USAHA SEBLAKMOMMY789 KABUPATEN SIDENRENG RAPPANG - Sapriani Sapriani; Muhammad Tamrin; Andi Riska Andreani Syafaruddin (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to identify marketing strategies on Instagram social media to increase brand awareness in the Seblakmommy789 business in Sidenreng Rappang Regency. The method used in this study is qualitative descriptive. The informants involved were selected through purposive sampling techniques, with a total of five people as data sources. Data was collected through observation, interviews, and documentation, and analyzed using Nvivo 12 software. The findings of the study show that the most effective digital marketing strategy through Instagram to increase brand awareness is to implement incentive programs such as giveaways. The results of the significant increase in brand awareness can be seen from the increase in product recalls